A new overlay P2P network for efficient routing in group communication with regular topologies. (3rd December 2019) - Hacini, Abdelhalim; Amad, Mourad
This research paper gives a new overlay P2P network to provide a performant and optimised lookup process. The lookup process of the proposed solution reduces the overlay hops and consequently the latency for content lookup, between any pair of nodes. The overlay network is constructed on top of physical networks without any centralised control and with a hierarchy of two levels. The architecture is based on regular topologies which are: the pancake graphs and the skip graphs. The focus of all topology construction schemes is to reduce the cost of the lookup process (number of hops and delay) and consequently improve the search performance for P2P applications deployed on the overlay network. Performance evaluations of our proposed scheme show that results obtained are globally satisfactory.